Reduction of Real Power Loss by using Comprehensive Neighbourhood Algorithm - Lenin, K.; Reddy, Bhumanapally Ravindhranath (International Journal of Computer (IJC), 2014)
In this paper, a new Comprehensive Neighbourhood Algorithm (CNA) is proposed to solve optimal reactive power dispatch problem. This algorithm is predominantly based on equilibrium between both the global and local search. A set of arbitrary solutions are primarily generated from the global search space, and then the best solution will give the optimal value. After that, the algorithm will iterate, and each iteration there will be two sets of generated solutions, one from the global search space and the other set of solutions will be produced from the neighbourhood of the best solution. The proposed Comprehensive Neighbourhood Algorithm (CNA) has been tested on standard IEEE 30, IEEE 57 bus test systems and simulation results show clearly thebetter performance of the proposed algorithm in reducing the real power loss.